Staying connected while social distancing - Hansen, Grace (Coronavirus (Abdo Kids), 2021)
This title begins by explaining what COVID-19 is, what social distancing is, what "flattening the curve" means, and how they're all related. It also gives kids fun ways to connect with their friends, extended family members, and neighbors who they likely miss seeing in person. The book gives kids both technology and technology-free options to stay connected with others.